Hepatitis G virus infections in Iceland - Love, A; Stanzeit, B; Gudmundsson, S; Widell, Anders (Journal of Viral Hepatitis, 1999)
This study describes the prevalence of hepatitisG virus (HGV) in Iceland, in blood donors and in persons with parenteral risk factors. Among 370 randomly selected Icelandic blood donors, the prevalence of HGV viraemia was 3.8%, whereas the prevalence of HGV antibodies in the same donor group was found to be 13.2%, thus indicating that at least 17% of blood donors in Iceland had previously been exposed to HGV. Previous exposure was seen in all age groups and also in older blood donors. Among intravenous drug users (IVDUs), the prevalence of HGV was much higher. Among 109 hepatitisC virus (HCV) antibody-positive serum samples collected in the years 1992-1997, 33. 9% were polymerase chain reaction (PCR)-positive for HGV and 48.6% had HGV antibodies. Thus, the pattern of HGV in IVDUs was similar to findings among IVDUs in other western countries. HGV viraemia was detected neither in 10 patients with haemophilia nor in five dialysis patients. However, six of the 10 haemophilic patients and one of the five dialysis patients had HGV antibody. In conclusion, unlike hepatitis C, which seems to have been introduced into Iceland relatively recently and has remained virtually confined to IVDUs, exposure to HGV is common among all age groups in the general population, suggesting that the virus has been prevalent in Iceland for much longer, making additional routes of transmission probable.